1977
DOI: 10.1007/bf02293745
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetric individual differences multidimensional scaling: An alternating least squares method with optimal scaling features

Abstract: Euclidian model, INDSCAL, measurement, similarities, data analysis, similarities data, quantification, successive block algorithm,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
393
1
9

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 859 publications
(413 citation statements)
references
References 42 publications
2
393
1
9
Order By: Relevance
“…This matrix was derived by subjecting participants' similarity ratings of emotion words to an individual-differences multidimensional scaling (INDSCAL) analysis using the ALSCAL procedure (Takane, Young, & DeLeeuw, 1976 emotion-related terms fell in a circular order around two dimensions. An inspection of this group solution suggested that one axis represented the valence denoted by the emotion terms, and the other corresponded to the level of arousal.…”
Section: Resultsmentioning
confidence: 99%
“…This matrix was derived by subjecting participants' similarity ratings of emotion words to an individual-differences multidimensional scaling (INDSCAL) analysis using the ALSCAL procedure (Takane, Young, & DeLeeuw, 1976 emotion-related terms fell in a circular order around two dimensions. An inspection of this group solution suggested that one axis represented the valence denoted by the emotion terms, and the other corresponded to the level of arousal.…”
Section: Resultsmentioning
confidence: 99%
“…INDSCAL weights have been used to index differential attention in previously published studies (e.g., Fazio & Dunton, 1997;Halberstadt & Niedenthal, 1997). In this study, the INDSCAL weights indexed individual differences in the semantic representation of emotionrelated words.The pre-and postsampling similarity ratings of emotion-related words were subjected to separate INDSCAL analyses using the ALSCAL procedure (Takane, Young, & DeLeeuw, 1976). The primary approach to ties (allowing data to become untied) was used in the analysis because it typically results in a better fit to the data (Davison, 1983, p. 86).…”
mentioning
confidence: 99%
“…In a first step, multi-dimensional scaling (MDS) using the ALSCAL algorithm (Takane, Young, & de Leeuw, 1977;Young, Takane, & Lewyckyij, 1978) is performed. For this, a distance matrix is developed for the content concepts, for which the process concepts serve as variables.…”
Section: Figure 1 Means Of Content and Process Concepts (N=24) Sortementioning
confidence: 99%